1990
DOI: 10.1067/mva.1990.24914
|View full text |Cite
|
Sign up to set email alerts
|

Does the end-to-end venous anastomosis offer a functional advantage over the end-to-side venous anastomosis in high-output arteriovenous grafts?

Abstract: This study explores the hemodynamics, mechanics, and biologic response of end-to-end versus end-to-side venous anastomoses in a canine arteriovenous graft model. Femoral polytetrafluoroethylene grafts were implanted bilaterally in a paired fashion (n = 22). Detailed local hemodynamic measurements were made by use of color Doppler ultrasound imaging at 1, 4, 8, and 12 weeks after implant. Measurements included volumetric flow rate and Doppler-derived spectral window (percent window) as a measure of turbulence. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0
1

Year Published

1993
1993
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(19 citation statements)
references
References 12 publications
1
17
0
1
Order By: Relevance
“…The dilemma of initial stent position during TIPS placement can have several clinical implications[22]. Andring et al[15] have shown that the hepatic venous end of TIPS stent graft position in relation to the hepatic vein and IVC junction has little effect on the primary patency rate following TIPS.…”
Section: Discussionmentioning
confidence: 99%
“…The dilemma of initial stent position during TIPS placement can have several clinical implications[22]. Andring et al[15] have shown that the hepatic venous end of TIPS stent graft position in relation to the hepatic vein and IVC junction has little effect on the primary patency rate following TIPS.…”
Section: Discussionmentioning
confidence: 99%
“…However, differences in relative amplitude and velocity of vessel wall movement indicated that anastomotic geometry may affect the pattern of hyperplastic response. 8 In a porcine aortic interposition graft model, data support the hemodynamic favorability of an acute anastomotic angle. 1 With 8 mm prosthetic grafts, end-to-side anastomoses were created at 90-degree, 45-degree, and 15-degree angles.…”
Section: Discussionmentioning
confidence: 83%
“…Animal experiment data were taken from the studies by Fillinger et al . in which pressures were measured in a canine model of the AV graft [4–6]. The following clinical and experimental data were incorporated as model parameters: mean arterial pressure, intragraft pressures, central venous pressure, initial graft blood flow, graft inner diameter, graft length, and final stenosis thickness.…”
Section: Methodsmentioning
confidence: 99%